The Role of the Free Nutritious Meal Program (MBG) in Optimizing the Nutritional Needs of Beginner Karate Athletes in Central Lombok Regency - Yusup, Novandi Firdaus; Ari, M. Azy; Yuliana; Hamzah (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to analyze the role of the Free Nutritious Meal Program (MBG) in optimizing the nutritional needs of beginner karate athletes in Central Lombok Regency. The research hypothesis states that there are significant differences in the indicators of athletes' nutritional needs before and after participating in the MBG program. The main problem behind this study is that the fulfillment of energy intake and body status of novice athletes is not optimal, even though the initial coaching phase requires adequate nutritional support to support training, recovery, growth, and performance readiness. This study uses a quantitative approach with a quasi-experimental one-group pretest-posttest design. The research subjects consisted of 30 beginner karate athletes who participated in the MBG program. Measurements were made through anthropometry to calculate Body Mass Index (BMI), a 24-hour dietary recall method for two non-consecutive days, namely weekdays and weekends, to estimate energy and nutrient intake, as well as a food consumption frequency questionnaire to see the athlete's diet. Data were analyzed using descriptive statistics, normality test, paired sample t-test, and Wilcoxon nonparametric test. The results showed that the average BMI increased from 17,270 in the pre-test to 17,880 in the post-test. The average energy intake also increased from 1702.67 kcal to 2270.00 kcal after the program. The results of the paired sample t-test showed a significant difference in BMI and energy with a p value of < 0.001. The Wilcoxon test also strengthened the findings with a p value of < 0.001. Thus, the research hypothesis is accepted. The MBG program has proven to play a positive role in improving the indicators of nutritional needs of beginner karate athletes, especially in terms of body status and energy adequacy. This program can be a supporting strategy for beginner sports coaching that is oriented towards health, training readiness, and long-term performance development. Keywords: free nutritious meal program; nutritional needs; beginner karate athletes; energy intake; body mass index.